Testing for Asymmetric Information Using "Unused Observables" in Insurance Markets: Evidence from the U.K. Annuity Market. Issue 4 (18th February 2014) - Finkelstein, Amy; Poterba, James
Abstract This article tests for asymmetric information in the U.K. annuity market of the 1990s by trying to identify "unused observables, " attributes of individual insurance buyers that are correlated both with subsequent claims experience and with insurance demand but that insurance companies did not use to set insurance prices. Unlike the widely used positive correlation test for asymmetric information, which searches for a positive correlation between insurance demand and risk experience, the unused observables test is not confounded by heterogeneity in individual preference parameters that may affect insurance demand. We identify residential location as an unused observable in the U.K. annuity market of this period. Even though residential location was observed by all market participants, the decision not to condition prices on it created the same types of market inefficiencies that arise when annuity buyers have private information about mortality risk. Our findings raise questions about how insurance companies select the set of buyer attributes that they use in setting policy prices. In the decade following the period that we study, U.K. insurance companies changed their pricing practices and began to condition annuity prices on a buyer's postcode.